Essays on the role of management control systems in innovation - Barros, Rúben Alexandre da Silva (2019)
The aim of this dissertation is to holistically explore the role of management control systems (MCS) in innovation. Following an increasing interest of the academic literature in this matter, we conducted an intensive and in-depth single case study in Amorim Cork Composites, a Portuguese company that is widely known as innovative. Until now the literature has established links between the four levers of control and the various types of innovation. However, it has been neglected that these systems were envisioned to work together and that their use generates important dynamic tensions. Therefore, informed by Simons’ framework we explore how the case company mobilizes the packages of MCS regarding innovation and the dynamic tensions that arises from these uses. Indeed, it is perceived that interactive and beliefs systems can create the necessary conditions and that diagnostic and boundary systems allow for the appropriation of the benefits of these conditions. After achieving these results, we then link institutional theory to the dimensions of communication and guidance/focus that come from data analysis to develop a model on how and why MCS affect the individuals’ behaviours. Based on institutional theory we argue that as a set of institutionalized routines MCS can orient individuals for innovation through the dimensions mentioned. Through cognition and sensemaking MCS increase the proactive behaviour of individuals to engage innovation. With this, we are able to present three inter-related essays (one literature review and two empirical essays) that contribute to advancing the existing knowledge and furthering the current debate on this subject.